CONSUMER BEHAVIOR IN INDUSTRIAL ERA 4.0 TO AVOID MARKET FAILURE - TITI RAHMAWATI; NUR AISYAH (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
Local governments should make policies related to market implementation that are closely related to economic aspects by focused on the orientation and behavior of consumer shopping in the industrial era 4.0. The style of shopping in the future in the era of industrial revolution 4.0 should be able to combine the style of online shop and physical shop. Both are complementary rather than replacing with regard to the concept of consumer satisfaction. This research aims to find out how much influence income redistribution, servicescape, festivalscape and experienscape have on efforts to prevent market failure. Research method with Kuantitative approach. The research sample of 200 traders in the Islamic market center Saporete Brebes obtained using Proportionate Stratified Random Sampling. The results showed that there was a weak and insignificant influence on efforts to avoid the failure of the Saporete Islamic Sunday Market Center Brebes Based on the results of multiple linear regression tests on servicescapes, experienscapes, festivalscapes and income redistribution together.